Creative Village Planning in an Effort to Support the Realization of Creative City - Khikmatul Islah; Ivan Budi Susetyo; Aryo Santiko (Yayasan Ilomata, 2021)
Population growth that continues to increase without being balanced with the extent of urban land causes an uncomfortable environment for all its society or communities. People need a chance to have a better life. Something new is required to solve this problem. One of the solutions is to create a Creative Village (Kelurahan Kreative), also as a form of support in realizing the Creative City. This study uses qualitative research with a literature study in data collection. The results show that this Creative Village can run with support from various parties; government, society, and the private sector. The collaboration of various parties will facilitate in realizing creative villages, which can be done by empowering the younger generation who are members of Karang Taruna (youth group). This young generation will move and develop the Creative Village. To support them, at first these young men will get various training as provisions. The use of technology is also important in efforts to realize Creative Village that will further support the creation of Creative City.